Implementasi Pendpidikan Guru Penggerak Sebagai Agen Perubahan ada SMP Negeri 1 Sekadau Hilir Kabupaten Sekadau - Sandri Hardiansah; Zulkarnaen Zulkarnaen; Erd Erd (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This research aims to analyze the implementation of the Guru Penggerak Training at SMP Negeri 1 Sekadau Hilir, Sekadau Regency. The study focuses on the effectiveness of Guru Penggerak as agents of change within the educational context. The main issues addressed are the imbalance in Guru Penggerak and the structural and cultural challenges hindering learning transformation. This study used a descriptive qualitative approach, collecting data through in-depth interviews, observations, and documentation. The findings show that Guru Penggerak has successfully implemented the “Merdeka Belajar” values and fostered change within the school environment. However, the implementation still faces obstacles such as heavy administrative workloads, resistance from some teachers, and a lack of institutional support. The study concludes that the effectiveness of Guru Penggerak as agents of change heavily relies on internal school collaboration, the leadership of the school principal, and supportive policies at the local level.